Facilitating dialogue between aquaculture and agriculture: Lessons from role-playing games with farmers in the Mekong Delta Vietnam - Dung, L.C.; Hoanh, Chu Thai; Page, C. le; Gajaseni, N. (IWA Publishing, 2009)
During the last few years, conflicts between agriculture and aquaculture have been an important issue in the Bac Lieu province, Mekong Delta, Vietnam. A large area of rice production has been converted to shrimp or shrimp–rice based production systems that require the intake of saline water into fresh water zones that have been used for agriculture. To manage this conflict, the provincial authorities have reviewed land use plans and identified a buffer zone with a mixed land use system of shrimp–rice (rice in the rainy season and shrimp in the dry season when sluices are opened). Under the CPWF (Challenge Program on Water and Food) Project No. 25, role playing games (RPGs) were applied for analyzing the land and water management strategy of farmers in the buffer zone. The RPGs organized in three villages (Phong Thanh, Ninh Thanh Loi and Vinh Loc) indicate that due to much higher revenue earned from shrimp compared with rice, farmers are attempting numerous techniques to prolong the duration of saline water in their fields for shrimp cultivation. This strategy makes the growing of a subsequent rice crop impossible even in the rainy season, thus requiring harmonization of water management at different levels (farm and canal systems). The results from these RPGs also indicate the need for further research on cultivation techniques for the shrimp–rice systems and on participatory methods to achieve better understanding of farmers' decisions.